Podnikatelský záměr na rozšíření firmy Kornfeil s.r.o. - Herůfek, Michal (Vysoké učení technické v Brně. Fakulta podnikatelská, 2007)
Bakalářská práce analyzuje otázku rozšíření a rozvoje sledované firmy. Obsahuje teoretické poznatky z oblasti podnikatelského záměru, analýzu současného stavu společnosti a návrh na rozšíření podnikání ve společnosti.

Bachelor´s Thesis analyses the question about expansion and development of the monitoring company. It contains teoretical finding from the sphere of business, analysis of the present state of company and proposal of development of business in the company.
Business Plan Of Development Of Company Kornfeil s.r.o.
Keywords: podnikatelský záměr; rozšíření firmy; ekonomická efektivita investice; business plan; development of company; economic effect of investment